An examination of the broader effects of warzone experiences on returning Iraq/Afghanistan veterans׳ psychiatric health. Issue 1 (30th March 2015) - Kimbrel, Nathan A.; DeBeer, Bryann B.; Meyer, Eric C.; Silvia, Paul J.; Beckham, Jean C.; Young, Keith A.; Morissette, Sandra B.
Abstract: The objective of the present research was to test the hypotheses that: (1) Iraq/Afghanistan war veterans experience a wide range of psychiatric symptomatology (e.g., obsessive–compulsive symptoms, hypochondriasis, somatization); and (2) general psychiatric symptomatology among Iraq/Afghanistan war veterans is associated with their warzone experiences. To achieve this objective, Iraq/Afghanistan war veterans ( N =155) completed a screening questionnaire that assessed a wide range of psychiatric symptoms along with a measure of warzone experiences. As expected, returning veterans reported significant elevations across a wide range of clinical scales. Approximately three-fourths screened positive on at least one clinical subscale, and a one-third screened positive on five or more. In addition, nearly all of these conditions were associated with veterans׳ warzone experiences (average r =0.36); however, this association was much stronger among veterans with posttraumatic stress disorder (PTSD) (average r =0.33) than among veterans without PTSD (average r =0.15). We also observed that approximately 18% of the variance in total psychiatric symptomatology was attributable to warzone experiences above and beyond the effects of childhood trauma and demographic factors. Taken together, these findings suggest that returning veterans experience a broad array of psychiatric symptoms that are strongly associated with their warzone experiences. Highlights: Iraq/Afghanistan veterans reported elevations on a wide range of clinical scales. Three-fourths of the sample exceeded the established cut-off for one clinical scale. One-third exceeded the established cut-off for five or more clinical scales. Total psychiatric symptoms were strongly associated with warzone experiences. The association between warzone experiences and psychiatric symptoms was strongest among veterans with PTSD.